Study of thermal migration and induced mechanical effects in double U-tube energy piles. (November 2017) - Luo, Jin; Zhao, Haifeng; Gui, Shuqiang; Xiang, Wei; Rohn, Joachim
Abstract: This paper investigates two geothermal energy piles using thermal response tests (TRTs). A set of parameters including pile wall temperature, ground temperature and strain are monitored at four different depths. The thermally induced mechanical behavior of the energy piles are then analyzed based on the monitoring data. The results show the following: (1) The temperature at the pile wall clearly varies throughout the heating and cooling cycle, and the ground temperature distribution shows a delay compared to the TRT stages. (2) The thermally induced mechanical effects are influenced by both the temperature and restraint conditions.